1968
DOI: 10.1126/science.162.3850.275
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Comparison of Hemoglobin Solutions and Erythrocyte Suspensions

Abstract: Hemoglobin solutions prepared from hemolyzed human erythrocyte packs have Newtonian flow properties. Diluted solutions are also Newtonian. All solutions have a viscosity lower than the apparent viscosity of erythrocyte suspensions of equal oxygen-carrying capacity. The presence of cell debris in hemoglobin solutions causes non-Newtonian (pseudoplastic or rheopectic) flow behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
89
0
2

Year Published

1970
1970
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(101 citation statements)
references
References 7 publications
10
89
0
2
Order By: Relevance
“…8). The data agree with those obtained by others on Hb AA (20,(23)(24)(25) as well as on Hb SA hemolysates (25). An increase in hemoglobin concentration up to the normal MCHC (32 g/100 ml) caused a relatively slight rise in viscosity, but further elevations in hemoglobin concentration resulted in a sharp increase in viscosity (Fig.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…8). The data agree with those obtained by others on Hb AA (20,(23)(24)(25) as well as on Hb SA hemolysates (25). An increase in hemoglobin concentration up to the normal MCHC (32 g/100 ml) caused a relatively slight rise in viscosity, but further elevations in hemoglobin concentration resulted in a sharp increase in viscosity (Fig.…”
Section: Resultssupporting
confidence: 82%
“…Therefore deformability of erythrocytes, a property which results in a lowering of viscosity at high shear rates (28), de- pends on the internal viscosity 2 of the hemoglobin-rich solution as well as on the flexibility of the membrane' (20,29,31,32 (Table II) and, according to the data shown in Fig. 8, presumably possess similar internal viscosities.…”
Section: Resultsmentioning
confidence: 99%
“…As presented in Table 1, we discover surprisingly high values for the effective viscosity (Ϸ100 ϫ 10 Ϫ3 Pa s) compared with literature values for RBC viscosity, which was reported to be approximately RBC Ϸ10 ϫ 10 Ϫ3 Pa s (18). Such an increase of the effective viscosity at the membrane was predicted to be a confinement effect caused by close association of the spectrin to the membrane, providing a steric obstacle for the fluid flow (19).…”
Section: Discussionsupporting
confidence: 51%
“…7 erythrocyte viscosity was constant between pH 6 (apparent intracellular pH = 6.30) and pH 8 (apparenit intracellular pH = 7.80), but increased dramatically at pH 5 (apparent intracellular pH = 5.32). Since the viscosity of hemiioglobin solutions at conicentrations approachinig those in the erythrocyte are four to five orders of magnitude less (29) than the estimated bulk viscositv of the membrane (30), this increase in erythrocyte viscosity is likely due, in part, to diminished miiemiibrane deformability. This conclusioni is supported by the observation that uinsealed ghosts isolated fromii erythrocytes exposed to pH 5 show a similar increase in viscosity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…But measurements of spectrin extraction from fresh and ATP-depleted ghosts as a function of extraction time showed that the decrease in spectrin extractability in the ATP-depleted sample, compared to normal, was evident throughout the extraction period. Extraction of spectrin from both samples reached a plateau by [20][21][22][23][24][25][26][27][28][29][30] h, well in advance of the time (40 h) when extractions were usually terminated (data not shown).…”
Section: Resultsmentioning
confidence: 99%